Building the state and conceiving the nation: the origins of separatist insurgency in the Mizo Hills, 1945-61. Issue 3 (3rd July 2022) - Holt, Benjamin
ABSTRACT: In 1966 the Mizo National Front (MNF) instigated a separatist conflict against the Indian state. This article argues that an environment conducive for separatist insurgency was created by the early 1960s in the Mizo Hills, a direct result of problematic state- and nation- building practices. First, there was an inability to initiate a successful state-building drive to overcome deep-seated challenges bestowed by colonial rule. Second, the friction between regional and national conceptions of identity was not resolved. This argument exploits a clear research gap. Currently there is a convincing explanation for the MNF's transition towards civil war between 1961-66. Yet, explaining the structural factors which created an environment conducive for separatist conflict remains elusive. This article plugs that gap, through archive-led historical analysis. In the process, it provides wider insights for conflict dynamics in India's northeast and raises broader questions about interdisciplinary research in the subfield of intrastate conflict.